Focal nodular hyperplasia that mimicked a liver metastasis from a soft tissue sarcoma: a case report - Masataka Amisaki; Soichiro Honjo; Noriyuki Iida; Satoshi Kuwamoto; Yoshiyuki Fujiwara (Surgical Case Reports)
Abstract Background Imaging modalities (computed tomography (CT), ultrasonography, and magnetic resonance imaging (MRI)) have only limited ability to distinguish liver focal nodular hyperplasia (FNH) from metastatic liver tumors. Here, we report a patient who underwent surgery for benign FNH that mimicked a liver metastasis from soft tissue sarcoma (STS). Case presentation A 23-year-old man with a history of several surgeries for metastatic abdominal STS, developed a hepatic tumor accompanying peritoneal STS recurrence. He was diagnosed with a metastatic liver tumor from the STS, based on imaging studies for the hepatic tumor that showed a growing hypervascular lesion and hypo-intensity in hepatic phase on dynamic CT and MRI. However, when the liver and peritoneal tumors were resected, histological diagnosis showed the hepatic tumor to be benign liver FNH. Conclusions Although FNH should be considered as a differential diagnosis for hypervascular hepatic tumors, it has few typical findings, and its appropriate management is controversial. A lesion strongly suspected of being a metastatic liver tumor might require surgical resection.